Effect of Chia (Salvia hispanica L) Addition on the Quality of Gluten-Free Bread - Steffolani, Maria Eugenia (2014)
The objective of this study was to analyze the influence of chia seeds and flour on the organoleptic quality of gluten-free breads. Rice breads were elaborated with the addition of 15 g of chia flour or seed, either dry or pre-hydrated, per 100 g of rice flour. The influence of the addition of chia on flour pasting properties and dough proofing behavior was analyzed. The specific volume, weight, texture, color and acceptability of the breads were studied. The addition of chia reduced specific volume and increased the hardness of breads, and the effect was more evident with the flour than with seed. Chia addition minimized weight loss during baking in all cases. The addition of chia flour produced a darker crust and crumb. There were no significant differences between the different breads in the global acceptability, but chia seed breads presented better values in terms of texture than control. Practical Applications This study shows that the use of chia seed and flours in rice bread making allows results in breads with good acceptability. However, the correct selection of seed or flours and previous hydration or not are essential to achieve appropriate results. Thereby, breads with chia seeds showed a better aspect valued by consumers, a higher specific volume and a lower firmness than breads made with chia flour, without a quality improvement in the case of a previous prehydration.